Characterization of the selected honeybee products based on omics techniques - Matuszewska, Eliza; Dereziński, Paweł; Klupczyńska, Agnieszka; Światły-Błaszkiewicz, Agata; Plewa, Szymon; Lubawy, Jan; Urbański, Arkadiusz; Rosiński, Grzegorz; Kokot, Zenon Józef; Matysiak, Jan (Journal of Medical Science, 2019)
to comprehensively characterize honeybee venom, royal jelly, propolis, and pollen, by applying advanced analytical and bioinformatics methodologies. Honeybee products (HBP) contain many bioactive components with both beneficial and harmful effects on the human organism. Nevertheless, the overall composition of the HBP remains not fully investigated. Thus, this research is focused on complementary proteomic and metabolomic characterization of biologically active compounds derived from HBP, regarding their toxicological and pharmacological properties. The objectives of the study will be achieved by the application of up to date mass spectrometry techniques. Due to increasing interest in using of HBP in medicine, this project will contribute to improving the safety of HBP‑derived dietary supplements and drugs.